K. Ujūr al-Shuhūr ʿalà Murūr al-Duhūr - Iṭfayyish, Muḥammad b. Yūsuf (al-Maṭb. al-Bārūniyya, 1893)
On the virtues of the month of Ramadan, with an accumulation of Traditions that have their equivalents in Sunni compilations.

Recueil de fables de La Fontaine traduites en kabyle, chaouia, m'zab, hébreu et arabe - Fredj, Adda (G. Heim, 1893)
Keywords: Linguistique -- Mzab

Zur Beurtheilung des Donatismus - Thümmel, Friedrich Wilhem (Ehrhardt Karras, 1893)
Keywords: Donatisme

Kitāb al-Ṣawm - Jannāwunī, Abū Zakariyyā’ Yaḥyà b. al-Khayr b. Abī ‘l-Khayr al- (Bārūniyya, 1893)
Keywords: Fiqh -- Libye -- 12e siècle

Handbook of British East Africa, including Zanzibar, Uganda, and the territory of the Imperial British East Africa company. - Foster (War Office, 1893)
Keywords: Zanzibar